Relationship between game-related statistics in elite men`s beach handball and the final result: a classification tree approach - Saavedra, J. M.; Pic, M.; Jimenez, F.; Lozano, D.; Kristjánsdóttir, H. (International Journal of Performance Analysis in Sport, 2019)
This study`s objectives were to (i) to compare beach handball game-related statistics by match outcome (winning and losing teams) and (ii) to develop a multivariate model explaining the performance in elite men`s beach handball. Seventy-two matches of the VIII Men`s Beach Handball World Championship held in Kazan (Russia) in 2018 were analysed. The dependent variable was match outcome (winning and losing teams), and the independent variables were the game-related statistics. A paired sample t-test was used to examine differences between teams. The effect sizes of the differences were calculated. The data were subjected to a multivariate analysis in the form of a regression and classification tree. The game statistics with the greatest effect size (ES=0.88) and which differentiated the winning and losing teams were the team`s overall valuation and total points. The classification and regression tree model correctly classified 94.5% of the records on the basis of eight variables distributed over 20 nodes: overall valuation, goalkeeper blocked spin-shots, goalkeeper received spin-shots, goalkeeper received one-pointer, spin-shot goals, specialist goals, blocks, technical fouls. Coaches could apply these results to seek better performance in the goalkeeper position and in two-pointer goals.